Implementasi Pelatihan Literasi Keuangan Syariah dalam Meningkatkan Pemahaman Ekonomi Islam di SMK Negeri 1 Dolok Masihul - Abdur Rahman Wahid Pulungan; Mutiah Khaira Sihotang (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe the implementation of Islamic financial literacy training and its impact on enhancing students’ understanding of Islamic economics at SMK Negeri 1 Dolok Masihul. The research employed a qualitative descriptive approach involving 25 students as participants. Data were collected through observation, interviews, questionnaires, and documentation. The results show that the training, conducted through interactive methods such as discussions, simulations, and case studies, significantly improved students’ knowledge of Islamic financial principles, including profit-sharing (mudharabah and musyarakah), prohibition of riba, and ethical financial management. The average understanding level increased from 63% before the training to 87% afterward. Supporting factors included teacher involvement, engaging materials, and the practical relevance of the content, while limiting factors were time constraints and lack of reference materials. Overall, the implementation of Islamic financial literacy training proved effective in strengthening students’ conceptual and practical understanding of Islamic economics and can serve as a model for integrating Sharia-based financial education in vocational schools.